Literature Review : Skrining Fitokimia Pada Berbagai Tanaman Obat Sebagai Sumber Senyawa Bioaktif - Nadia Safitri; Riska Hidayah; Nita Triadisti (Jurnal Riset Multidisiplin Edukasi, 2025)
Phytochemical screening is a crucial preliminary step in identifying secondary metabolites from medicinal plants that serve as potential bioactive compounds for the development of traditional and modern medicines. This review summarizes findings from 25 national and international journals that investigated various plant sources, including leaves, flowers, seeds, fruits, stems, and even microalgae. The most commonly analyzed compounds include flavonoids, alkaloids, tannins, saponins, steroids, triterpenoids, polyphenols, glycosides, and anthraquinones. The results indicate that flavonoids and tannins are the most frequently detected metabolites, both of which are known for their antioxidant, antimicrobial, anti-inflammatory, and wound-healing properties. Variations in metabolite content among plants are influenced by species, plant parts used, extraction methods, and the choice of solvents, with ethanol being the predominant solvent. Several studies also complemented the screening with biological activity assays, such as DPPH antioxidant testing, antibacterial assays, and wound-healing studies, further supporting the therapeutic potential of these compounds. This review highlights the importance of phytochemical screening as a scientific foundation for the development of phytopharmaceuticals and the utilization of Indonesia’s rich biodiversity.